"As High as I Could:" Media Discourse Shaping Patricia Okoumou's Statue of Liberty Protest. Issue 4 (8th August 2022) - Grant, Rachel; Brown, Vicki
ABSTRACT: News coverage around monuments and statues have served as spaces of resistance for marginalized communities. The Statute of Liberty protest of Patricia Okoumou challenged the U.S. immigration policies by connecting collective memory to media narratives. This paper argues that competing understandings of Okoumou's protests appeared in mainstream media and the social media platform, Twitter. In response, Okoumou would start her own website and blog in order to illuminate herself as a voice of authority. This paper builds on the reinforced understandings of the racialized protests and how Black women engage in these discussions on social media. In order to keep her message clear, Okoumou created a digital space to oppose the mainstream media message. Thus, this study adds to the centering of Black women's bodies as a form of discourse of experiences and self-definition because Okoumou declared her existence and rose to find her voice on her personal digital platforms.